See complete Problem 110

Contact Triangle, Area, Incircle. Level: High School, SAT Prep, College geometry

Post your solutions or ideas in the comments.

Subscribe to:
Post Comments (Atom)

skip to main |
skip to sidebar
## Tuesday, May 27, 2008

###
Geometry Problem 110

## Link List

Online Geometry theorems, problems, solutions, and related topics.

See complete Problem 110

Contact Triangle, Area, Incircle. Level: High School, SAT Prep, College geometry

Post your solutions or ideas in the comments.

Subscribe to:
Post Comments (Atom)

For trigonometry lovers!

ReplyDeleteTriangles ADE,BDF,EFC are isoscele,hence we know the angles.

ADF=90+B/2;DFC=90+B/2;DEF=(A+C)/2

S=(1/2)ED*EF*sin(DEF)

DE=2ADsin(A/2)=2(p-a)sin(A/2)

EF=2ECsin(C/2)=2(p-c)sin(C/2)

after substitution

S=(p-a)(p-b)(p-c)/(2R)

because

(p-b)=(a-b+c)/2=R(sinA-sinB+sinC)

(p-b)=4Rsin(A/2)cos(B/2)sin(C/2)

S'=(1/2)AD*DF*sin(ADF)

S''=(1/2)CF*DF*sin(DFC)

after substitution and simplification

2S'S''/(S'+S'')=AD*DF*FC*sin(B/2)/b

=(p-a)(p-b)(p-c)/(2R)

because

b=2RsinB and 2sin(B/2)cos(B/2)=sinB

with Heron's formula we can say

S=[ABC]r/(2R)

the transformation of (p-b) is made by

sinp+sinq=2sin((p+q)/2)cos((p-q)/2)...

Let A=Area of Tr. ABC. Using standard notation, A^2=s(s-a)(s-b)(s-c). Also A=r*s where r=inradius and s=semiperimeter as usual. Thus,

ReplyDelete(rs)^2=s(s-a)(s-b)(s-c) or r^2*s=(s-a)(s-b)(s-c). We now use the result of Problem #82 whereby S/A=r/2R or S=rA/2R=(r^2*s)/2R =(s-a)(s-b)(s-c)/2R or 2/S=4R/[(s-a)(s-b)(s-c)]-----(1).

Now draw a perpendicular,h, from D to BC. We've S1=h*AD/2=h(s-a)/2. Like wise, S2=h(s-c)/2 since Tr. BDF is isosceles and thus 1/S1+1/S2=2[1/(s-a)+1/(s-c)]/h=2b/[sin(B)(s-a)(s-b)(s-c)]. But b/sin(B)=2R hence 2/S =4R/[(s-a)(s-b)(s-c)]-----(2). By equations (1) & (2), we've 2/S = 1/S1 + 1/S2 ; hence etc.

Antonio, if there's still an easier way to do this, would you be kind enough to show us the same?

Ajit

Suggestions for another solution:

ReplyDelete1. The area of a triangle is equal to one half of the product of its altitude and base.

2. Similar triangles.

3. The two tangents to a circle from an external point are congruent.

One more solution as suggested by Antonio: In the given diagram, let FD and CA (both extended) meet in V and let angle DVA=Θ & VA=x. Draw perpendiculars h1, h & h2 to FD extended from A, E & C resply. Now proving that S=2S1/(S1+S2) is tantamount to proving h = 2h1h2/(h1+h2) since the three triangles have a common base FD.

ReplyDeleteApply Menelaus's Theorem to Tr. ABC with FDV as the transversal, we've:x/(x+b)*(s-c)/(s-b)*(s-b)/(s-a)=1(ignoring the - sign which is unimportant here). This gives us x/(x+b) =(s-a)/(s-c).

Note that AD=AE=(s-a), CE=CF=(s-c) & BF=BD=(s-b) where 2s=a+b+c. Now, h1=(x)sin(Θ), h2=(x+b)sin(Θ) while h=(x+s-a)sin(Θ). Substitute the values above to eliminate x & s to obtain: h=[b^2 -(a-c)^2]sin(Θ)/2(a-c) & 2h1h2/(h1+h2) also =[b^2-(a-c)^2]sin(Θ)/2(a-c). In other words, h = 2h1h2/(h1+h2) or S = 2S1S2/(S1+S2)

Ajit

I propose an alternative solution to problem 110, following the idea showed by Ajit, with slightly different termination.

ReplyDeleteLet h, h1 and h2 be the altitudes EG, AJ and CK, of triangles DEF, ADF and DFC, respectively, related to the common base DF. Take H on the extension of AJ, with AH = 2*h1. Take I such that HI is parallel to DF and CI is perpendicular to DF. We have CII = h1 + h2.

If we prove that h = 2*h1*h2/(h1 + h2), this implies that S = 2*S1*S2/(S1 + S2).

The extension of KJ meets the extension of CA at V. The extension of IH meets the extension of CA at W. Putting AV = x, we have AW = 2x. Let’s use the Menelaus’ theorem to triangle ABC, with the transversal DF, which meets AB at D, BC at F, and CA at V: (AD/DB)(BF/FC)(CV/VA) = 1, or [(s-a)/(s-b)]*[(s-b)/(s-c)]*[(x+b)/x] = 1, where s is the semi perimeter of ABC. Thus, x/(x+b) = (s-a)/(s-c), and x = b*(s-a)/(a-c) (1).

We have EG/CK = h/h2 = VE/VC = (x+s-a)/(x+b). Substituting (1) and simplifying the result, we get h/h2 = 2*(s-a)/b.

We have also AH/CI = 2*h1/(h1+h2) = AW/CW = 2x/(2x + b). Substituting (1) and simplifying the result, we get 2*h1/(h1+h2) = 2*(s-a)/b.

So, h/h2 = 2*h1/(h1+h2) and finally h = 2*h1*h2/(h1 + h2).